Um Estudo de caso sobre a interação máquina-máquina na perspectiva dos algoritmos clássicos de geração de caminhos livres de colisão - Batista, Josias Guimarães (2017)
This paper presents a proposal for the implementation of the Articial Potential Fields algorithm (APF) in a SCARA manipulator (Selective Compliant Assembly Robot Arm).We explore a case study on the machine-machine interaction, represented by the manipulator and a mobile robot. This study was carried out through the implementation of the APF algorithm, which is a classic algorithm, the same is used in the generation of collision free paths in a dynamic environment, monitored by an image sensor, in real time.. Several approaches are explored between the manipulator and the mobile robot. These approaches, which take into account the combinations between the mobile robot and the manipulator as the extended body and point. The algorithm was implemented in the manipulator to generate the collision-free, dynamic obstacle paths with random positions, in real time. The results show the eciency of the algorithm with respect to productivity and were satisfactory in this case study. We also present the results of the eciency of the algorithm through OEE (Overall Equipment Eectiveness), the energy consumption and the results of the error analysis between the positions generated by the power eld algorithm and the actual positions of the manipulator.